Keanekaragaman Jenis Tumbuhan Paku (Pteridophyta) di Jalur Pendakian Selo Kawasan Taman Nasional Gunung Merbabu, Jawa Tengah - Astuti, Fitri Kusuma; Murningsih, M; Jumari, J (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2018)
Indonesia has a very high biodiversity, as well as ferns (Pteridophyta).Selo climbing lane at Merbabu Montain Nasional Park selected as the study site because of the many ferns that were founded in this area.The purpose of this study was to analyze the diversity of ferns species.in tropical rain forest ecosystem of high mountains and sub-alpine forests ecosystem on Selo climbing lane at Merbabu Mount National Park. There are many human activity in Selo climbing lanesupposed to influence the existing plants. This research was held on August-December 2016. The method usedinventory inSelo climbing lane and Plot, then analyzed using diversity index. The results found 33 species of ferns from 15 families. The diversity of ferns in the tropical rain forest ecosystem of high mountains fall into the medium category except at post II (2412 masl) has low diversity. Diversity in the sub-alpine forest ecosystem can not be calculated.Â Key word: diversity, fern, Selo climbing lane.